Cultural and entertainment programs on television: problem and prospects of functioning - Кіца, Мар’яна; Куль, Марія; Kitsa, Mariana; Kul, Maria (Видавництво Львівської політехніки, 2021)
Культурно-розважальні програми займають важливу нішу на телебаченні. Більшість молоді віддає перевагу саме такому жанру. Через це, щоб зацікавити аудиторію такою передачею, потрібно докласти великих зусиль при створенні розважального сюжету. Зважаючи на те, що розважальні телепередачі набувають популярності, кожне шоу має бути індивідуальним і відповідно відрізнятися одне від одного. Стосовно рекомендацій, котрі ми б хотіли зробити для покращення культурно-розважальних програм, це насамперед мова. Мовлення телебачення розглядають як важливий фактор емоційної взаємодії трьох елементів – зображення, звуку і слова. Проте найважливіше значення в сучасному телебаченні відіграє слово, воно є головним “інструментом” майстерності журналіста. Прагнення до чистоти мовлення, його зрозумілості – один з основних професійних принципів тележурналістів. Як показує аналіз ток-шоу, майстерний ведучий є запорукою успіху телепередачі. Ведучий – це людина, яка насамперед є обізнаною і постійно збагачує свої знання в професійному руслі. Це особа, яка має професійні навики, а саме: володіння інтонацією та тембром голосу, манера жестикуляції перед камерою і сама робота з камерою. Ведучий – це творча людина, яка виконує роботу журналіста, режисера, оператора та редактора. Ведучий має бути розумним, ненудним, талановитим та енергійним. Адже, саме таких людей вимагає глядач в телепередачі. Ведучі мають розвивати думку, інтерпретувати події та проводити ефіри з природньою манерою та інтонацією. Ведучий, безумовно, є представником певної соціальної групи, і його взаємодію можна розглядати як, “представницьке спілкування”, тобто спільні інтереси, цінності, ідеали і настанови цієї групи. Він повинен сам представляти себе глядачеві як партнера у спілкуванні. Встановлення міжособистісних контактів у процесі телевізійного спілкування відбувається завдяки аудіовізуальному характеру телевізійної комунікації. Глядач одержує повідомлення від конкретної особи, ведучого телевізійної передачі, саме тому таке повідомлення має персоніфікований характе

Today, cultural issues should be one of the most popular among the viewers of the Ukrainian channels, because such programs affect the level of their education and culture in general. Modern globalization has determined the specifics of socio-cultural dynamics, and media play an important role in this process, demonstrating a channel of translation of the values and content of mass culture, whose stereotypes are widely disseminated in the socio-cultural space. Media in modern society have a significant impact on the formation of value orientations. Cultural and entertainment programs occupy an important niche on television. Most young people prefer this genre. Therefore, to interest the audience in such a program, you should make great efforts to create an entertaining story. As entertainment TV shows become popular, each show must be individual and different from each other. As for the recommendations we would like to make to improve cultural and entertainment programs, this is first and foremost a question. Television speech is seen as an important factor in the emotional interaction of the three elements – image, sound and word. But the word plays the most important role in modern television, it is the main “tool” of a journalist’s skill. The desire for purity of speech, its intelligibility – one of the basic professional principles of television journalists. As the analysis of the talk show shows, a skilled presenter is the key to the success of a TV show. The presenter is a person who is first of all aware and constantly enriches his knowledge in a professional way. This is a person who has professional skills, namely: mastery of intonation and timbre of the voice, the manner of gesturing in front of the camera and the work with the camera. A presenter is a creative person who works as a journalist, director, cameraman and editor. The presenter must be smart, not boring, talented and energetic. After all, such people are required by the viewer in a TV show. Hosts should develop thinking, interpret events and conduct broadcasts in a natural manner and intonation. The presenter, of course, is a representative of a certain social group, and his interaction can be considered as “representative communication”, meaning the common interests, values, ideals and guidelines of this social group. He must present himself to the viewer as a partner in communication. The establishment of interpersonal contacts in the process of television communication is due to the audiovisual nature of television communication. The viewer receives a message from a specific person, the host of a television program, which is why such a message is personalized. Nowadays we can talk about the tendencies of increasing their influence on the formation of general public flavors and needs, as a result of which research and systematization of mechanisms of interaction of mass media and culture in the process of the emergence of modern values is an urgent problem.
Культурно-розважальні програми на телебаченні: проблеми та перспективи функціонування
Keywords: культура; телебачення; розвага; шоу; аудиторія; ведучий; culture; TV; entertainment; show; audience; presenter; 007; 304; 659.3